Contribution Of Copper Smelting Technology To Sustainable Development Of Human Society (Yazawa Symposium) - Akira Nishikawa (The Minerals, Metals and Materials Society, 2003)
During the twentieth century the copper smelting industry achieved dramatic expansion corresponding to the vast growth of global economy. This was largely due to innovations in pyro-metallurgical processes, such as autogenous smelting and continuous smelting and converting technologies. However, as copper production capacity increased, its impact on the environment also could not be ignored, and thus with increasing global environmental awareness, many smelting operations either had to renew or rebuild their facilities. In addition to these changes, in places like Japan and Europe, with scarce primary resources, the treatment and recovery of metals from a variety of items such as car shredder dust, used electrical appliances and electronic devices, on top of scraps traditionally treated, is having a profound effect on the reduction of waste and the preservation of primary resources. Thus compared to the days when copper smelting focused on the environmental control in order to break with "Smoke Stack Industry", copper smelting today is making an important contribution to the sustainable development of human society.